2006
DOI: 10.1007/s10725-005-5481-7
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipids as Plant Growth Regulators

Abstract: In this paper the potential to use phospholipids and lysophospholipids as plant growth regulators is discussed. Recent evidence shows that phospholipids and phospholipases play an important signalling role in the normal course of plant development and in the response of plants to abiotic and biotic stress. It is apparent that phospholipase A (PLA), C (PLC) and D (PLD), lysophospholipids, and phosphatidic acid (PA) are key components of plant lipid signalling pathways. By comparison, there is very little inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
58
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 92 publications
0
58
0
1
Order By: Relevance
“…Furthermore, 680 mg l Ϫ1 KH 2 PO 4 , was quite effective for proliferation of the bamboo cells. Phosphate sources were well known as essential constituents for the regulation of cell growth and/or metabolic activities in plant species (Cowan 2006;Hagimori et al 1982;Sugiyama et al 1986). MSp680 medium condition allows the supply of homogenous bamboo cells within 14 d. Furthermore, histological observation using LSM clearly indicated that the cells have active proliferation capacity during days 8-14 of the culture period.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 680 mg l Ϫ1 KH 2 PO 4 , was quite effective for proliferation of the bamboo cells. Phosphate sources were well known as essential constituents for the regulation of cell growth and/or metabolic activities in plant species (Cowan 2006;Hagimori et al 1982;Sugiyama et al 1986). MSp680 medium condition allows the supply of homogenous bamboo cells within 14 d. Furthermore, histological observation using LSM clearly indicated that the cells have active proliferation capacity during days 8-14 of the culture period.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, exogenously applied PA stimulated those enzyme activities . The use of exogenous PLs as regulators of plant growth is in its infancy (Cowan, 2006). Exogenous PA can couple to intracellular agents to initiate signaling systems.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous PA can couple to intracellular agents to initiate signaling systems. The understanding of the effect of exogenous PL on endogenous PL homeostasis and coupling to endogenous lipid-signaling networks needs further investigation (Cowan, 2006). Because PA applied directly to the medium may be metabolized in the medium or during entry into cells , we checked the quality of the exogenously applied PA after treating cucumber explants for 1 h at 25°C and found that it remained unaltered throughout the experiment (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is now evident that lipids and their metabolites play important role in other critical cellular functions particularly as mediators in cell activation, signal transduction, and cell proliferation (Cowan, 2006;Divecha and Irvine, 1995;Ryu et al, 1997). Lysophosphatidy-lethanolamine (LPE) is a natural product of membrane phospholipid metabolism and is formed from phosphatidylethanolamine (PE) by action of phospholipase A 2 and remains in the lipid phase because LPE has a hydrophobic group such as fatty acid.…”
Section: Introductionmentioning
confidence: 99%